Simpson grade 3 resection does not improve clinical outcome in neglected thoracic psammomatous spinal meningioma? A case report. (2019) - Azharuddin, Azharuddin; Hutagalung, Muhammad Bayu Zohari; Kamarlis, Reno Keumalazia
Highlights: Thoracic spinal psammomatous meningioma is a rare subtype of meningioma often present with pain, sensory-motor deficit, and sphincter disturbance. Neglected spinal cord compression can result in a permanent neurological deficit. Surgical resection of the tumor relieved the spinal cord in a neglected case. The severe preoperative neurological deficit as a predictor of a poor prognosis. The neurological function after surgery hardly returns to the functional stage in a neglected case. Abstract: Introduction: Thoracic spinal psammomatous meningioma is a rare subtype of meningioma. Surgery is the definitive treatment for symptomatic spinal meningiomas and offers a substantial possibility for complete resection and cure. Presentation of case: A 42-year-old female complaining of back pain for one year and progressive weakness and numbness of both lower limbs with urinary incontinence and constipation for two months. Magnetic resonance imaging showed an intramedullary spinal mass at D3-D4 level. The patient underwent laminectomy at D3-D5 level, revealing dural bulge. A midline durotomy performed. Intraoperative findings showed firmed, greyish to white and moderately vascular mass. A clear margin was identifiable between cord and tumor. Simpson grade 3 resection was performed. Pedicle screw and rod was placed for posterior stabilization. Histopathological examination demonstrated a psammomatous spinal meningioma. Despite the pain and the sensory sensation was improved, the motoric and autonomic function still showed no significant improvement in the early postoperative period. Discussion: The preferred approach or procedure must be tailored case by case based on preoperative surgical grading of the tumor and its associated factors. Meanwhile, the prognosis for recovery depends mainly on two factors: the severity of the neurological deficit and the duration of the deficit before decompression. Conclusion: Surgical resection of the tumor may relieve the spinal cord compression in a neglected case. Even though the neurologic function after surgery rarely returns to the functional stage due to chronic neural tissue damage.